Bariatric surgery diminishes spinal diagnoses in a morbidly obese population: A 2-year survivorship analysis of cervical and lumbar pathologies. (August 2021) - Passias, Peter G.; Alas, Haddy; Kummer, Nicholas; Krol, Oscar; Passfall, Lara; Brown, Avery; Bortz, Cole; Pierce, Katherine E.; Naessig, Sara; Ahmad, Waleed; Jackson-Fowl, Brendan; Vasquez-Montes, Dennis; et al.
Highlights: After weight-loss surgery, patients no longer sought care for their spinal diagnosis Lumbar herniation had higher resolution than cervical herniation by 90 days. Cervical degeneration and stenosis resolved at higher rates than lumbar pathologies. Abstract: The effects of bariatric surgery on diminishing spinal diagnoses have yet to be elucidated in the literature. The purpose of this study was to assess the rate in which various spinal diagnoses diminish after bariatric surgery. This was a retrospective analysis of the NYSID years 2004–2013. Patient linkage codes allow identification of multiple and return inpatient stays within the time-frame analyzed (720 days). Time from bariatric surgery until the patient's respective spinal diagnosis was no longer present was considered a loss of previous spinal diagnosis (LOD). Included: 4, 351 bariatric surgery pts with a pre-op spinal diagnosis. Cumulative LOD rates at 90-day, 180-day, 360-day, and 720-day f/u were as follows: lumbar stenosis (48%, 67.6%, 79%, 91%), lumbar herniation (61%, 77%, 86%, 93%), lumbar spondylosis (47%, 65%, 80%, 93%), lumbar spondylolisthesis (37%, 58%, 70%, 87%), lumbar degeneration (37%, 56%, 72%, 86%). By cervical region: cervical stenosis (48%, 70%, 84%, 94%), cervical herniation (39%, 58%, 74%, 87%), cervical spondylosis (46%, 70%, 83%, 94%), cervical degeneration (44%, 64%, 78%, 89%). Lumbar herniation pts saw significantly higher 90d-LOD than cervical herniation pts (p < 0.001). Cervical vs lumbar degeneration LOD rates did not differ @90d (p = 0.058), but did @180d (p = 0.034). Cervical and lumbar stenosis LOD was similar @90d & 180d, but cervical showed greater LOD by 1Y (p = 0.036). In conclusion, over 50% of bariatric patients diagnosed with a cervical or lumbar pathology before weight-loss surgery no longer sought inpatient care for their respective spinal diagnosis by 180 days post-op. Lumbar herniation had significantly higher LOD than cervical herniation by 90d, whereas cervical degeneration and stenosis resolved at higher rates than corresponding lumbar pathologies by 180d and 1Y f/u, respectively.